The effects of vertically oriented resistance training on golf drive performance in collegiate golfers - Driggers, A. R.; Sato, K. (International Journal of Sports Science & Coaching, 2018)
The purpose of this study was to examine the effects of vertically oriented resistance training on golf driving performance. Ten Division-I collegiate golfers completed two resistance training sessions per week for 10 weeks during the fall tournament season. Pre- and post-training assessments of strength-power and golf performance were compared. To assess strength-power, jump height, peak force, and peak power were measured from static and countermovement vertical jumps; peak force and rate of force development from 0 to 250ms were measured from an isometric mid-thigh pull. Golf performance was assessed in terms of ball launch speed, spin rate, carry yardage, and total yardage, averaged from five shots using a driver. Following training, all measures of strength-power improved, with countermovement jump peak power improving significantly (p<0.00625). The golf performance assessment indicated significant increases (p<0.0125) in ball speed, carry yardage, and total yardage. These results suggest that vertically oriented resistance training can improve golf driving performance